Guide to Biomass comminution : material properties, machinery, principles of the process and fundamentals of process modelling - Niedzwiecki, Lukasz (Bachelor Thesis, 2013)
This study aims to derive a qualitative model for energy requirements of the wood chipping process. A relationship is shown between energy requirements and properties of biomass, which is a quite variable material. The relationship between comminution machinery and energy which is necessary for the process is highlighted. The derivation of the model is focused on chipping, but it is generally possible to make it available for both different types of biomass (f. ex. agricultural residues)and different types of comminution machinery (f. ex. hammermills) by using different material properties adju.